Bioactive Compounds from the Zingiberaceae Family with Known Antioxidant Activities for Possible Therapeutic Uses - Raphael N. Alolga; Feizuo Wang; Xinyao Zhang; Jia Li; Lam-Son Phan Tran; Xiaojian Yin (MDPI AG, 2022)
The Zingiberaceae family is a rich source of diverse bioactive phytochemicals. It comprises about 52 genera and 1300 species of aromatic flowering perennial herbs with characteristic creeping horizontal or tuberous rhizomes. Notable members of this family include ginger (Zingiber officinale Roscoe), turmeric (Curcuma longa L.), Javanese ginger (Curcuma zanthorrhiza Roxb.), and Thai ginger (Alpinia galanga L.). This review focuses on two main classes of bioactive compounds: the gingerols (and their derivatives) and the curcuminoids. These compounds are known for their antioxidant activity against several maladies. We highlight the centrality of their antioxidant activities with notable biological activities, including anti-inflammatory, antidiabetic, hepatoprotective, neuroprotective, antimicrobial, and anticancer effects. We also outline various strategies that have been applied to enhance these activities and make suggestions for research areas that require attention.